Examining the impact of celebrity endorsement on student’s purchase intention of smartphone / Zarith Delaila Abd Aziz and Zarith Thuraya Abd Aziz - Abd Aziz, Zarith Delaila; Abd Aziz, Zarith Thuraya (Universiti Teknologi MARA, 2021)
Consumers in Malaysia have witnessed the use of smartphone expand dramatically and companies hire celebrity as their brand endorser to promote the smartphones. Substantial dollars has been spent on celebrity endorsement as marketing tactics. Hence, it is importance to understand it success. The objectives of this study is to examine the extent at which university students have been impacted by celebrity endorsements on their purchase intention for smartphones. Quantitative method and survey were used to captured 119 data from respondents. The results revealed that celebrity attractiveness has the greatest impact on the purchase intention of smartphones meanwhile celebrity trustworthiness shows the lowest impact on students. The results of this study provides an exclusive viewpoint concerning students’ purchase intention on smartphones and assists the marketing practitioners to better understand the use of celebrity endorsement